ChemInform Abstract: First Incorporation of the Tetrahedral [Sn4]4‐ Cluster into a Discrete Solvate Na4[Sn4]·(NH3)13 from Solutions of Na4Sn4 in Liquid Ammonia. Issue 38 (30th August 2013) - Waibel, Markus; Faessler, Thomas F.
Abstract Na4[Sn4]·13NH3 is obtained from deep red suspensions of Na4Sn4, Cu‐Mst, and 18‐crown‐6 in liquid NH3 (‐70 °C, 19 weeks, 25% yield).